Use of NDVI-adjusted PAR for predicting gross primary production in a temperate grassland in Iceland - Rannveig Ólafsdóttir 1984-; Hlynur Óskarsson 1960- (2014)
Gross primary production (GPP) is an important variable to estimate in the global carbon cycle. Estimates of GPP at regional to global scales are critical for understanding ecosystem response to an increased atmospheric CO2 level and for providing objective information for political decisions. The best approach for calculating GPP is through direct measurements of small areas, using either the static-chamber method or eddy covariance technique. Calculating GPP of a whole ecosystem or an entire region is on the other hand problematic. However, scaling up GPP, estimated from direct ground measurements, has increasingly played a role in ecosystem characterization (Lischke et al. 2007). Given that vegetation productivity is directly related to the amount of solar radiation within the plant canopy (Knipling 1970), the simplest method for predicting GPP would be a mathematical function derived from a direct correlation between measured GPP and photosynthetically active radiation (PAR). Many approaches to estimate GPP have been developed based on the work of Monteith (1972), where he suggested that GPP can be expressed as a product of fraction of absorbed photosynthetically active radiation (fAPAR), incident photosynthetically active radiation (PARin) and light use efficiency (LUE), which is the efficiency of the absorbed PAR converted into biomass. Yet an estimate of solar radiation, such as PAR, is not a sufficient indicator of photosynthesis at high northern or southern latitudes because fluctuations in vegetation green mass and solar radiation are not synchronous in time. Several studies have suggested a new remote technique to relate GPP to a product of chlorophyllrelated vegetation indices (VI) and incoming photosynthetic radiation, GPP ∞ VI x PARin, based on Monteith’s logic (Wu et al. 2009, Gitelson et al. 2006, Peng et al. 2013). Numerous vegetation indices are known to indicate the chlorophyll content of vegetation, such as the Red Edge Chlorophyll Index (CIred edge), MERIS terrestrial chlorophyll index ...